DAMPAK SOSIAL EKONOMI TERHADAP ADANYA WISATA SUNGAI BONO DI KELURAHAN TELUK MERANTI KECAMATAN TELUK MERANTI KABUPATEN PELALAWAN - Mega Silvia Hutauruk; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted in the bay village of Meranti, a bay in Meranti Pelalawan District. The purpose of this study was to determine the characristics of Bono river tourism and the socio economic impact of local communities, the sample in this study amounted to 48 respondent. The outher uses the data instrument is questionnaire observation and documentation. From research conducted by authors found that socio economic income was minimal before the existence of the Bono River, and we can compare it after the existence of the Bono River. And the people in the Teluk Meranti Village rose 75% after the Bono River. And the Bono River, and the increase in visits of tourists from outside the city and from within the city, therefore the traders from outside the city and from within the city, therefore the traders and business owners of the community’s socio economic income are increasing their social economic income. Keywords: Social Economy Impact River Bono Tourism